Transboundary animal diseases - Grace, Delia; Dessie, Tadelle; Dione, Michel M.; Kiara, Henry K.; Liljander, Anne M.; Mariner, Jeffrey C.; Naessens, Jan; Okoth, Edward; Patel, Ekta; Steinaa, Lucilla; Toye, Philip G.; Wieland, Barbara (CAB International, 2020)
Transboundary animal diseases (TADs) are highly contagious epidemics with the potential for very rapid spread, causing serious economic and sometimes public health consequences while threatening farmers' livelihoods. TADs often cause high morbidity and mortality in susceptible animal populations. Some TADs are also emerging infectious diseases, food-borne diseases and/or zoonoses: these are covered in other chapters. This chapter covers those high-impact, highly contagious animal diseases, such as foot-andmouth disease (FMD), that do not infect humans but do affect food and nutrition security and trade that the International Livestock Research Institute (ILRI) has been working on since the 1990s. These are: African swine fever (ASF), mycoplasma disease (both contagious bovine pleuropneumonia (CBPP) and contagious caprine pleuropneumonia (CCPP)), peste des petits ruminants (PPR) and Newcastle disease (ND). Other TADs, which were to a lesser degree the focus of ILRI research, are briefly mentioned (including FMD, classical swine fever (CSF) and rinderpest).